Tense and Aspect of English In Pedagogical Grammar: How essential are they for EFL Learners in Indonesia - Jufrizal Jufrizal (Universitas Negeri Padang, 2014)
Tense, aspect, and modality are those of universal grammatical features which make specific characteristics on human languages cross-linguistically. As a tenseness language, English grammatically constructs the tense, aspect, and modality in sentential constructions in different ways compared with those of bahasa Indonesia and most of local languages in Indonesia which belong to tenseless languages. The grammatical strategies used by English concerning with tense, aspect, and modality should be intentionally and academically learned in any program of English learning. This paper discusses the grammatical features tenses and aspects of English on the particular perspectives of pedagogical grammar. This paper continuously analyzes the how essential the understanding on English tenses and aspects is for EFL learners in Indonesia as the way of building and strengthening grammatical competence and language awareness. It is scientifically believed that the descriptive and pedagogical perspectives on English tenses and aspects are academically and psychologically essential for EFL learners in this country